2003
DOI: 10.1046/j.1365-2133.2003.05511.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations in acute arsenic poisoning from the Wakayama curry-poisoning incident

Abstract: Our observations indicate that skin lesions are common in patients with acute arsenic poisoning; these findings may provide information of diagnostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 10 publications
1
44
0
Order By: Relevance
“…7 Subsequently, the connection between herpetic skin lesions and acute arsenic poisoning has been shown, both for simplex and zoster eruptions. 8,9 However, as environmental arsenic poisoning becomes uncommon and the therapeutic use of arsenic archaic, this association has been all but forgotten. J AM ACAD DERMATOL VOLUME 53, NUMBER 5 Brief reports 891…”
Section: Discussionmentioning
confidence: 99%
“…7 Subsequently, the connection between herpetic skin lesions and acute arsenic poisoning has been shown, both for simplex and zoster eruptions. 8,9 However, as environmental arsenic poisoning becomes uncommon and the therapeutic use of arsenic archaic, this association has been all but forgotten. J AM ACAD DERMATOL VOLUME 53, NUMBER 5 Brief reports 891…”
Section: Discussionmentioning
confidence: 99%
“…Initial clinical signs of acute or sub-acute arsenic induced gastrointestinal disturbances including excessive salivation, nausea, thirst, burning lips, swallowing problems, gastrointestinal cramps, abdominal pain, dehydration and severe diarrhea were reported (Ratnaike, 2003;Uede and Furukawa, 2003;Vantroyen et al, 2004). Typical symptoms of dyspepsia were reported in 60 people (38.4%) while screening a group of arsenic (0.05-3.2mg/L) exposed individuals (n=156) in West Bengal, India (Mazumder et al, 1998).…”
Section: Effects Of Arsenic On Endocrine Systemmentioning
confidence: 99%
“…(Guo et al, 2007). It is evident that skin lesions are commonly observed in patients exposed to acute arsenic exposure (Uede and Furukawa, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the biological defense mechanisms against high-dose arsenic have not been well studied using animal models. However, in Japan, there have been several tragic cases of high-dose arsenic intoxication, including the large-scale contamination of milk powder (Dakeishi et al, 2006) and a curry-poisoning incident (Uede and Furukawa, 2003). Although cellular-level studies showed that the Keap1-Nrf2 system protects cells against acute arsenite toxicity (Shinkai et al, 2006;Wang et al, 2007), but there not yet any in vivo evidence to support the protective effects of Nrf2.…”
Section: Introductionmentioning
confidence: 99%